2007
DOI: 10.1158/1078-0432.ccr-07-2141
|View full text |Cite
|
Sign up to set email alerts
|

Is Cell Death a Critical End Point for Anticancer Therapies or Is Cytostasis Sufficient?

Abstract: Since the discovery of conventional chemotherapy and the development of new target-based agents, the importance of cytostasis in anticancer activity has been debated. This review examines the relative importance of both cytostasis and cytotoxicity based on both preclinical data and clinical reports. Several limitations of our basic and clinical methods to evaluate cytostasis and cytotoxicity will be highlighted. Molecular mechanisms of cytostasis will be analyzed, including interference with the cell cycle as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
119
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 51 publications
(46 reference statements)
0
119
1
2
Order By: Relevance
“…[18][19][20] There is a long-lasting conceptual discussion of whether cytotoxic and cytostatic drugs should be combined. 33 The term "cytostatic drugs" has been used for drugs that act against tumor cells by inducing cell-cycle arrest. In our study, anthracyclines arrested the cell cycle and behaved like cytostatic drugs in the cell lines investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] There is a long-lasting conceptual discussion of whether cytotoxic and cytostatic drugs should be combined. 33 The term "cytostatic drugs" has been used for drugs that act against tumor cells by inducing cell-cycle arrest. In our study, anthracyclines arrested the cell cycle and behaved like cytostatic drugs in the cell lines investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cytostatic and cytotoxic behaviour plays an important role in the progression of a drug into preclinical and clinical studies. Cytostatic drugs have been found to be metastases preventative and increase the survival rates of patients by delaying the time to disease progression [17]. Cytotoxic drugs, on the other hand, are less selective and the induced cell death could be more detrimental to the patient in terms of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic drugs, on the other hand, are less selective and the induced cell death could be more detrimental to the patient in terms of side effects. Rixe and Fojo (2007) found that a drug elicited either cytostatic or cytotoxic cellular responses depending on its active concentration [17].…”
Section: Introductionmentioning
confidence: 99%
“…These data would be indicative of the cytotoxic and cytostatic effects of NAAm in human PBLs. Rixe and Fojo (2007) reported that cytostaticity may be defined as the inhibition of cell growth and/or proliferation, and this initial event can induce cell death if cytostasis is prolonged. Accordingly, in the present study, NAAm revealed a cytostatic effect for the 24 h exposure period without cytotoxicity, whereas this compound displayed both cytostatic and cytotoxic properties for 48 h treatment period due to prolonged exposure of the test substance on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%